Difficulties in Applying Critical Thinking Skills in Teaching Arabic at the Basic Education Stage from the Perspective of Subject Teachers in Misurata (Sirte University Journal of Humanities, 2024)
This research aims to identify the challenges of applying critical thinking skills in teaching Arabic language in primary education from the perspective of teachers in Misrata city. To achieve the research objectives, the researcher used a descriptive approach through a questionnaire developed by Al-Anzi (2011). The questionnaire consisted of a set of items related to the difficulties of applying critical thinking skills in teaching Arabic in primary education, categorized into three domains: the teacher, the student, and the curriculum. The questionnaire was distributed – after ensuring its validity and reliability – to a sample of 150 Arabic language teachers in primary education in Misrata city (Misrata Central Education Services Office) to determine their opinions on the research topic. Data were analyzed statistically using the Statistical Package for the Social Sciences (SPSS). The research revealed several key findings: the overall score for the difficulties in applying critical thinking skills was high, with a relative weight of 77%. Difficulties related to the curriculum ranked first with a high score and a relative weight of 80%. Difficulties related to the student came second with a moderate score and a relative weight of 77.3%, while difficulties related to the teacher ranked third with a moderate score and a relative weight of 73.3%.
Keywords: Difficulties; Critical thinking; Arabic language